A Development of online Activities Package with Embedded System Board to Enhance Coding Skill for Elementary Student - Nilkong, Panadda; Manosuttirit, Artnarong (Journal of Technical and Engineering Education, 2025)
This research was research and development (R&D) purposes of this study were: 1) to study the elements of Online Activities Package with Embedded System Board to Enhance Coding Skill for Elementary Student 2) to development of Online Activities Package with Embedded System Board to Enhance Coding Skill for Elementary Student to achieve effectiveness according to the criteria E1/E2 = 80/80 3) to study the progress of learners after using the Online Activities Package with Embedded System Board to Enhance Coding Skill for Elementary Student. The Population used in the research was 72 Elementary student. A sample was selected from 30 students in the science club who were ready and volunteered by purposive sampling. Statistical analysis involves mean, standard deviation (S.D.), and E1/E2 performance test. The results of this study indicate that: 1 The results elements of Online Activities Package; 1) Activity set name 2) Recommendations for teachers and students 3) Time 4) Learning objectives 5) Pre-test and Post-test 6) handout 7) Learning activities 8) Media and equipment 2. The testing of the effectiveness of Online Activities Package the E1/E2 criteria, with scores (82.83/83) 3. Learners who learned with the online activity set had an increase in knowledge of .7026 or 70.26 percent and learners had good coding skills (average = 2.62) or 87.43 percent.